The Learning Revolution: Investigating the Use of Technology to Explore Mathematical Physics Learning - Pratiwi, Hestiningtyas Yuli; Sujito, Sujito; Sunardi, Sunardi; Sayyadi, Muhammad (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
This research aims to describe how future physics teachers study mathematical physics. Physics students must master the existing material in Mathematical Physics mathematics well, thoroughly, and collaboratively. Data collection is done with lifts, interviews, and observations. Research results show that the learning process needs to be more contextual, less applicative, and highly dominant in mathematics; less attractive teaching materials and lectures are not designed to equip students with the skills of the 21st century. Learning does not use technology to help students solve physical problems. It causes students difficulty learning mathematical methods in physics. In fact, in learning mathematical physics, students must master the concepts related to mathematics tools and their applications. The ability to mathematically solve problems of physical phenomena and give meaning to mathematical models is built into critical aspects of learning. The solution that can be applied is to apply technology using software applications like Maple.